2019
DOI: 10.3390/su11123304
|View full text |Cite
|
Sign up to set email alerts
|

Responsible or Thematic? The True Nature of Sustainability-Themed Mutual Funds

Abstract: The aim of the paper is to compare the risk-adjusted performance of sustainability-themed funds with other categories of mutual funds: sustainable and responsible mutual funds that implement different approaches in portfolio selection and management, and thematic funds not committed to responsible investments. The study analyses a sample of about 1000 European mutual open-end funds where 302 are sustainability-themed funds, 358 are other responsible funds, and 341 other thematic funds. Risk-adjusted performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…However, our research indicated that managers investing globally or on Europe and Japanese markets may narrowly beat the market. Additionally, we confirmed that SRI funds perform better during a crisis, and achieve average results or underperform the market in non-crisis periods which is consistent with several prior studies [30,33,81,82]. As far as the industry factor is concerned, our results are consistent with the findings of Busse and Tong [83] who proved the importance of industry-selection skill for fund performance and with the studies of Jin and Han [35] on the positive correlation between that green funds preference and innovation indicators in the Chinese market.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our research indicated that managers investing globally or on Europe and Japanese markets may narrowly beat the market. Additionally, we confirmed that SRI funds perform better during a crisis, and achieve average results or underperform the market in non-crisis periods which is consistent with several prior studies [30,33,81,82]. As far as the industry factor is concerned, our results are consistent with the findings of Busse and Tong [83] who proved the importance of industry-selection skill for fund performance and with the studies of Jin and Han [35] on the positive correlation between that green funds preference and innovation indicators in the Chinese market.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several authors have indicated that SRI funds perform better during a crisis, when it is possible to outperform the market. However, funds achieve average results or even underperform the market in non-crisis periods [30,33,81,82]. In our research, the alpha parameter confirmed the relationship mentioned above because we mainly covered periods of increases in the market, in particular in the North America region.…”
Section: Relative Performancesupporting
confidence: 79%
“…From this point of view, fund portfolios that concentrate all their stocks mainly in one specific sector, such as the healthcare or biotechnology sectors, could lose investment opportunities generated in other sectors, increasing their idiosyncratic risk, which lessens funds' risk-adjusted return. Recent empirical evidence provides support for modern portfolio theory in the energy sector [2][3][4] and in other specific sectors analyzed as a group [7], assuming that the state of the economy remains unchanged over time in global markets. However, managers usually adjust their management strategy to the economic situation by incorporating a dynamic trading strategy into the fund portfolios.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 82%
“…This study adds to previous finance literature by being, to the best of our knowledge, the first to analyze the financial performance of sustainable development goals (SDG)-related funds (so called thematic mutual funds) focused on the biotechnology and healthcare sectors (SDG 3). While previous studies have focused on analyzing SDG funds related to the water sector [1], the renewable energy sector [2][3][4][5][6] or several thematic sectors as a group [7], limited attention has been paid to mutual funds focused on sustainable development goals in the area of health, although the United Nations encourages the private sector to contribute to progress towards sustainable development goals by also investing in firms related to healthcare issues.…”
Section: Introductionmentioning
confidence: 99%
“…Federica Ielasi and Monica Rossolini in their research made a conclusion that sustainability-themed mutual funds are more similar to other thematic funds. The authors made the performance analysis and stressed that such funds can give better results during financial crisis and that have extra benefits from SRI regulation and disclosure [49].…”
Section: Sustainability 2020 12 X For Peer Review 7 Of 20mentioning
confidence: 99%